Restricting biofuel imports in the name of the environment: how does the application of WTO rules affect developing countries? - Ahamat, Haniff; Abdul Rahman, Nasarudin (Yijun Institute of International Law, 2014)
There are calls for biofuel imports from countries to be restricted. The imports which are either in the form of end-product (biothanol or biodiesel)or feedstock (oil palm, sugar cane molasses, etc) are allegedly produced in ways which can threaten the environment and violate human rights. This article finds that there is no specific regime for trade in biofuels within the WTO system. Hence any restriction on such trade is governed by the existing trade regimes including tariffs and non-tariff measures. However, the existing WTO tariff and non-tariff (TBT, anti-dumping and anti-subsidy)regimes are still inadequate in ensuring that measures are taken against biofuel feedstock and products that were produced in sustainable ways. The use of these measures without being subject to clear defining rules will create a danger that they serve a protectionist rather than social or environmental objectives.